2006
DOI: 10.2106/jbjs.f.00001
|View full text |Cite
|
Sign up to set email alerts
|

Mechanobiology of the Intervertebral Disc and Relevance to Disc Degeneration

Abstract: Mechanical loading of the intervertebral disc may contribute to disc degeneration by initiating degeneration or by regulating cell-mediated remodeling events that occur in response to the mechanical stimuli of daily activity. This article is a review of the current knowledge of the role of mechanical stimuli in regulating intervertebral disc cellular responses to loading and the cellular changes that occur with degeneration. Intervertebral disc cells exhibit diverse biologic responses to mechanical stimuli, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
144
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(151 citation statements)
references
References 30 publications
4
144
0
Order By: Relevance
“…Predictably, at both the mRNA and protein level, there was robust expression of GlcAT-I in nucleus pulposus cells of both the neonatal and mature rat discs; the protein was also expressed by cells of the annulus fibrosus. This latter observation was not unexpected, since the inner annulus, like the nucleus, is rich in proteoglycans (1,2). Gain and loss of function experiments were performed to learn if calcium flux induced transcriptional activation of GlcAT-I reporter activity and if this activation was regulated by TonEBP.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Predictably, at both the mRNA and protein level, there was robust expression of GlcAT-I in nucleus pulposus cells of both the neonatal and mature rat discs; the protein was also expressed by cells of the annulus fibrosus. This latter observation was not unexpected, since the inner annulus, like the nucleus, is rich in proteoglycans (1,2). Gain and loss of function experiments were performed to learn if calcium flux induced transcriptional activation of GlcAT-I reporter activity and if this activation was regulated by TonEBP.…”
Section: Discussionmentioning
confidence: 95%
“…Although sparse, cells in the nucleus pulposus secrete a complex extracellular matrix that contains fibrillar collagens and the proteoglycan aggrecan. Glycosoaminoglycan (GAG) 2 components of the aggrecan molecule provide a robust hydrodynamic system that serves to accommodate applied biomechanical forces (1,2). Surprisingly, although the importance of aggrecan secretion and function has been discussed by many investigators, mechanisms of control of GAG synthesis are poorly understood.…”
mentioning
confidence: 99%
“…Lumbar intervertebral discs change morphologically, biochemically, and biomechanically with advancing age, [1][2][3][4][5][6][7][8][9][10] changes that are characterized as disc degeneration and are implicated as the origin of low back pain. Unfortunately, the initiating and perpetuating factors of disc degeneration are unknown, so despite the pain, disability, and economic loss associated with disc degeneration, intervention and mitigation strategies cannot effectively proceed.…”
mentioning
confidence: 99%
“…This hypothesis is supported by experimental animal models [25][26][27] and epidemiological data, linking heavy lifting, intense physical work, and obesity with increaseing rates of LBP [28][29][30]. Supra-physiologic movements like bending, rotation, and compression can lead to structural defects associated with degeneration of the IVD [31]. A recent study has also shown that intense physical stress can induce a catabolic response characterized by increasing protease gene and protein expression/activity [32].…”
Section: Aging Of the Vertebral Discmentioning
confidence: 86%